2011
DOI: 10.1097/jcn.0b013e31820e2fae
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Intimacy Among Patients With Implantable Left-Ventricular Assist Devices

Abstract: Three themes emerged from the data: (a) improved sexual relations with LVAD, (b) sexual adjustment, and (c) nonsexual intimacy. The themes identified were consistent with the concept of normalcy from the theory of self-care. Participants reported that as the LVAD improved their overall health, their sexual functioning also improved. Participants also reported an increased sense of connectedness and intimacy with their partners even in the absence of sexual intercourse. Participants discussed ways in which they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…7,18 All studies reported methods to maintain qualitative rigor as measured by the CASP, but the article by Sandau was most transparent, reporting attributes of the non-clinician interviewers and more details regarding the grounded theory approach (see Table 1). 7,8,1822 Sample sizes ranged from 5-12 patients with a total of 59 patients included in the 7 studies (see Table 2). The mean age of participants was 52.3 years and 25% (n=15) were women.…”
Section: Resultsmentioning
confidence: 99%
“…7,18 All studies reported methods to maintain qualitative rigor as measured by the CASP, but the article by Sandau was most transparent, reporting attributes of the non-clinician interviewers and more details regarding the grounded theory approach (see Table 1). 7,8,1822 Sample sizes ranged from 5-12 patients with a total of 59 patients included in the 7 studies (see Table 2). The mean age of participants was 52.3 years and 25% (n=15) were women.…”
Section: Resultsmentioning
confidence: 99%
“…161 After LVAD placement, there may be renewed interest in sexual activity, improved sexual desire, and more energy to engage in sex, whereas before implantation of the LVAD, the debilitating symptoms of HF may have prevented patients from engaging in or thinking about sex. Partners reported being somewhat anxious about intercourse, mainly because of fears of causing harm, injury, or death.…”
Section: Left Ventricular Assist Devicesmentioning
confidence: 99%
“…Finally, despite cardiac transplantation and implantation of left ventricular assistance devices has improved survival and overall QoL in patients with terminal heart failure, their effects on sexual activity is not clearly defined, depending probably by the individual emotional response to such invasive therapies (Basile et al, 2001;Marcuccilli et al, 2011). Nevertheless, in these patients physical activity is usually encouraged and, as a consequence, sexual activity is not contraindicated.…”
Section: Potential Additional Treatments For Hf and Edmentioning
confidence: 99%